A sex‐specific feedback projection from aromatase‐expressing neurons in the medial amygdala to the accessory olfactory bulb. Issue 3 (27th August 2021) - Inbar, Tal; Davis, Rachel; Bergan, Joseph F.
Abstract: The accessory olfactory bulb (AOB) plays a critical role in classifying pheromonal signals. Here we identify two previously undescribed sources of aromatase signaling in the AOB: (1) a population of aromatase‐expressing neurons in the AOB itself; (2) a tract of aromatase‐expressing axons which originate in the ventral medial amygdala (MEA) and terminate in the AOB. Using a retrograde tracer in conjunction with a transgenic strategy to label aromatase‐expressing neurons throughout the brain, we found that a single contiguous population of neurons in the ventral MEA provides the only significant feedback by aromatase‐expressing neurons to the AOB. This population expresses the estrogen receptor alpha (ERα) and displayed anatomical sex differences in the number of neurons (higher in male mice) and the size of cell bodies (larger in females). Given the previously established relationship between aromatase expression, estrogen signaling, and the function of sexually dimorphic circuits, we suggest that this feedback population is well‐positioned to provide neuroendocrine feedback to modulate sensory processing of social stimuli in the AOB. Abstract : Aromatase neurons are distributed in clustered populations primarily in a network of brain regions (red) devoted to social behavior. Out of all potential sources of aromatase neurons, only the ventral medial amygdala projects back to the accessory olfactory bulb. The population of aromatase‐expressing neurons in the ventral medial amygdala also expresses ERα and displays two sex differences: (1) aromatase‐expressing neurons are larger in females; (2) there are more aromatase‐expressing neurons in male mice.